Aflibercept, bevacizumab or ranibizumab for diabetic macular oedema: recent clinically relevant findings from DRCR.net Protocol T. Issue 6 (November 2017) - Cai, Sophie; Bressler, Neil M.
Abstract : Purpose of review: The aim of this study was to provide clinically relevant findings from the DRCR.net Protocol T, a multicentre randomized clinical trial comparing intravitreous aflibercept, repackaged (compounded) bevacizumab and ranibizumab for vision-impairing centre-involved diabetic macular oedema (DME). Recent findings: At 1 year, all three antivascular endothelial growth factor (anti-VEGF) drugs, on average, improved visual acuity. There was no difference among drugs in mean change in visual acuity from baseline among eyes with baseline Snellen equivalent visual acuity of 20/32 to 20/40, whereas aflibercept yielded superior vision outcomes among eyes with baseline visual acuity of 20/50 to 20/320. At 2 years, aflibercept remained superior, on average, to bevacizumab, but not ranibizumab, among eyes with baseline visual acuity of 20/50 to 20/320. Over 2 years, in post-hoc area-under-the-curve analysis, aflibercept vision outcomes were superior to bevacizumab or ranibizumab among these eyes. All three drugs had comparable ocular and systemic safety profiles. The substantial cost differential between aflibercept and bevacizumab raises challenges when safety and efficacy are at odds with cost-effectiveness results. Summary: When initial visual acuity loss is mild, there are no apparent differences, on average, among aflibercept, bevacizumab and ranibizumab for treating DME. When visual acuity loss is moderate or worse, aflibercept is more likely to improve visual acuity.